Disseminated tumor cells and enhanced level of some cytokines in bone marrow and peripheral blood of breast cancer patients as predictive factors of tumor progression - Semesiuk, N.; Zhylchuk, A.; Bezdenezhnykh, N.; Lykhova, A.; Vorontsova, A.; Zhylchuk, V.; Kudryavets, Y. (Experimental Oncology, 2013)
Background: In recent years, the presence of disseminated tumor cells (DTC) in bone marrow (BM) of patients with breast cancer (BC) is considered as an important clinical feature of the distribution process. However, relapse often occurs in spite of the negative results of the bone marrow cytology. This suggests the need to find additional signs of the possibility for predict the recurrence. Aim: to detect DTC in BM and determinate cytokine status of peripheral blood (PB) and BM of primary BC patients for prognosis of tumor recurrence. Patients and methods: 72 BC patients with histologically proven diagnosis were enrolled into study. 31 patients with progression of disease and 41 patients with clinical stabilization (conditional remission) were included to “progression” and “remission” group respectively. This division of BC patients was conditional and was made during the 3 years study. The presence of DTC in BM was detected by immunocytochemical analysis. Plasma levels of TNF-α, M-CSF, IFN-α were defined by bioassay tests. Plasma levels of IL-6, TGF-β1 and VEGF were determined by ELISA. BM and PB BC patients were obtained before treatment. Results: In our study DTC in samples of BM were detected in 50% BC patients of progression group. It was found that most significant addition markers of tumor progression with presence of DTC in BM are the levels of cytokines such as TNF in BM and PB, CSF-1 and IL-6 in PB and endogenous IFN in BM and PB of BC patients. In patients of disease “progression” group the levels of TNF in BM were increased by 45.8% (p < 0.01), the levels of CSF-1 and IL-6 in PB were increased more than by 70–80% (p < 0.05). Conclusion: Comprehensive detection DTC in BM and identification the level of TNF, IFN, CSF-1, IL-6 in PB and BM of BC patients could be one of the ways for prognosis the metastatic process and correction antitumor individualized therapy.